The acceptability of medicinal plant gardens: Healers' perspective from Nkomanzi East Region - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Dissertation (M Inst Agrar ( Agricultural Extension))--University of Pretoria, 2005.